The hourglass pattern of women's representation. Issue 3 (3rd July 2019) - Kjaer, Ulrik; Kosiara-Pedersen, Karina
ABSTRACT: Women's descriptive underrepresentation in parliaments is traditionally presented as the result of a process that discards women as they move up the ladder of recruitment. In this article, the case of Denmark is used to demonstrate an alternative hourglass pattern where women's presence does decrease in the early phases but increase in the later phases. There are fewer women among party members than among party voters, and fewer women among potential candidates than among party members. However, there is a higher share of women among nominated candidates than among potential candidates, and women are more likely than men to get elected. This hourglass pattern is found at the aggregate level as well as across political party and over time. There are two implications of this finding: (1) the traditional pyramidal pattern cannot be taken for granted, and (2) in countries where women's representation follows an hourglass shape, scholars and advocates alike should focus on membership recruitment by political parties and on internal party processes that aim to develop party members' willingness to run for political office prior to the formal nomination process.